2014
DOI: 10.1021/es500934s
|View full text |Cite
|
Sign up to set email alerts
|

20th Century Atmospheric Deposition and Acidification Trends in Lakes of the Sierra Nevada, California, USA

Abstract: We investigated multiple lines of evidence to determine if observed and paleo-reconstructed changes in acid neutralizing capacity (ANC) in Sierra Nevada lakes were the result of changes in 20th century atmospheric deposition. Spheroidal carbonaceous particles (SCPs) (indicator of anthropogenic atmospheric deposition) and biogenic silica and δ13C (productivity proxies) in lake sediments, nitrogen and sulfur emission inventories, climate variables, and long-term hydrochemistry records were compared to reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…, Heard et al. ). Moat Lake was selected because it has a history of water chemistry sampling, is N‐limited, and is relatively accessible (~1.5 mile hike).…”
Section: Methodsmentioning
confidence: 99%
“…, Heard et al. ). Moat Lake was selected because it has a history of water chemistry sampling, is N‐limited, and is relatively accessible (~1.5 mile hike).…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics limit a lake's ability to neutralize acid rain and a watershed's ability to sequester nutrients or contaminants. Metals, organochlorines, and other persistent organic pollutants recorded in mountain lake sediment cores chronicle the increase, and subsequent, regulatory decrease, of these substances in society (Fernandez et al, 2000;Camarero et al, 2009;Usenko et al, 2010;Heard et al, 2014). Some of these compounds can be more abundant in mountain lakes than at lower elevations due to cold condensation, a phenomenon where organochlorines that volatilize in warm environments move into mountain areas with air currents and condense at colder temperatures (Blais et al 1998).…”
Section: Sensitivity and Susceptibility Of Mountain Lakes To Atmosphementioning
confidence: 99%
“…A recent analysis of 14 metropolitan areas in the U.S. concluded that 60-80% of the impacts of urban emissions occur outside of the urban zone (Heo et al, 2017). Emissions reductions of SO 2 and NO x have caused deposition of SO 4 2− and NO 3 − to decline considerably across most of the U.S. (Vet et al, 2014), even in remote mountain regions (Heard et al, 2014), while increased production of NH 3 from agriculture and vehicles has caused an increase in chemically-reduced forms of N deposition (Thiruvengadam et al, 2016). Moreover, while the effects of N deposition on aquatic and terrestrial ecosystems are well known, these broad patterns are complicated by growing evidence that reduced forms of N cause more severe ecosystem responses than oxidized N forms (Dias et al, 2014;Glibert, 2010;Kleijn et al, 2008;Mur et al, 2017;Stevens et al, 2011;Van den Berg et al, 2005Verhoeven et al, 2011).…”
Section: Environmental and Ecological Implications Of Urban And On-romentioning
confidence: 99%
“…Air pollution is also an important issue for the many local, state and national parks and other public and private recreational areas that are in regions where air quality, regional haze, visibility impairment and N deposition impacts are strongly affected by urban and on-road emissions. Particulate forms of N also allow for long-range transport of atmospheric N, thus contributing to N deposition effects in wildland areas located downwind of emission sources (Heard et al, 2014;Hertel et al, 2013).…”
Section: Environmental and Ecological Implications Of Urban And On-romentioning
confidence: 99%